Changes in Production Potential in China in Response to Climate Change from 1960 to 2010 - Luo Liu; Xi Chen; Xinliang Xu; Yong Wang; Shuang Li; Ying Fu (Advances in Meteorology)
From the Global Agro-Ecological Zone (GAEZ) model, changes in the three climate factors (temperature, precipitation, and solar radiation) over the past five decades showed different trends and that production potential was impacted significantly by the geographic heterogeneity of climate change. An increase of approximately 1.58 million tons/decade in production potential correlated with climate change. Regions with increased production potential were located mainly in the Northeast China Plain, the northern arid and semiarid region, and the Huang-Huai-Hai Plain. Regions with decreased production potential were located mainly in the Middle-lower Yangtze Plain and southern China. The climate factors that impacted production potential varied by region. In the Northeast China Plain, increased temperature was the major cause of the increased production potential. In the northern arid and semiarid region, temperature and precipitation were the major factors affecting production potential, but their effects were in opposition to each other. In southern China, increased temperature and decreased solar radiation caused a decreased production potential. In the Middle-lower Yangtze Plain, a decrease in solar radiation was the major factor resulting in decreased production potential. In the Huang-Huai-Hai Plain, changes in temperature and solar radiation had large but opposite effects on production potential.